How important are spillovers from major emerging markets? - Raju Huidrom; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
The seven largest emerging market economies -China, India, Brazil, Russia, Mexico, Indonesia, and Turkey- constituted more than one-quarter of global output and more than half of global output growth during 2010-15.These emerging markets, which we call EM7,are also closely integrated with other countries, especially with other emerging and frontier markets. Given their size and integration, growth in EM7 could have significant cross-border spillovers. We provide empirical estimates of these spillovers using a Bayesian vector auto regression model. We report three main results. First, spillovers from EM7 are sizeable: a 1 percentage point increase in EM7 growth is associated with a 0.9 percentage point increase in growth in other emerging and frontier markets and a 0.6 percentage point increase in world growth at the end of three years. Second, sizeable as they are, spillovers from EM7 are still smaller than those from G7 countries (Group of Seven of advanced economies). Specifically, growth in other emerging and frontier markets, and the global economy would increase by one-half to three times more due to a similarly sized increase in G7 growth. Third, among the EM7, spillovers from China are the largest and permeate globally.
Keywords: E32; F20; F42; 330; Business cycles; spillovers; externalshocks; China; EM7; G7; Konjunkturzusammenhang; Konjunktur; Spillover-Effekt; Schock; China; Indien; Brasilien; Russland; Mexiko; Indonesien; Türkei